Enhancing students' communication skill by creating infographics using Genially in learning climate change. Issue 1 (March 2021) - Azizah, D N; Rustaman, N Y; Rusyati, L
Abstract: This study is aiming to investigate students' communication skill in terms of verbal and visual on learning climate change topic as a socio-scientific issue. The communication skill attainment was assessed by incorporating infographics generated using Genially website. The research was conducted due to its significant role of the skill for students to become empowered global citizens in 21st century that requires the ability to communicate information to be easily understood and perceived concisely by the audience. The research method used is one group pre-post-test to investigate the enhancement of students' ability before and after the experimental treatment. However, the result shows a good enhancement on average score for both verbal and visual competency areas with certain activities to sustain the whole communication skills.